Synthesis of high‐surface area mesoporous SiC with hierarchical porosity for use as catalyst support. Issue 10 (29th June 2020) - Ortega‐Trigueros, Adrian; Narciso, Javier; Caccia, Mario
Abstract: Porous SiC with a hierarchical mesoporous structure is a promising material for high‐performance catalytic systems because of its high thermal conductivity, high chemical inertness at high temperature, and oxidation resistance. Attempts to produce high‐surface area hierarchical SiC have typically been made by using porous carbon as a template and reacting it with either Si or SiO2 at high temperature under inert atmosphere. Because the reaction mechanism with Si involves a carbon dissolution step, and the reaction with SiO2 is highly dependent on C‐SiO2 dispersion, the porous structure of the carbon template is not maintained, and the reaction yields nonporous SiC. In this work, mesoporous SiC has been synthesized using a novel hard‐template methodology. SiC was prepared from hierarchical (mesoporous) silica which served as a solid template. Carbon deposition was done by Carbon Vapor Deposition (CVD) using CH4 as carbon precursor, where different temperatures and reaction times were tested to optimize the carbon coating. The synthesized SiC retained 61 (118 m 2 /g) and 47% (0.3 cm 3 /g) of the BET surface area and the mesopore volume of the original SiO2, which is 10 times higher than the retention reported for other template methods used to produce high surface area SiC.